Scrolling for fun or to cope? Associations between social media motives and social media disorder symptoms in adolescents and young adults - Thorell, Lisa B.; Autenrieth, Milena; Riccardi, Alice; Burén, Jonas; Nutley, Sissela B. (Frontiers in Psychology, 2024)
Although not yet recognized as an official disorder, Social Media Disorder (SMD) has recently received considerable interest in the research. However, relatively little is known about underlying motives for social media use and to what extent motives show differential associations with SMD symptom severity and SMD diagnosis. The overall aim of the present study was therefore to examine motives for social media use in relation to 1) which motives are most common, 2) associations between motives and both SMD symptom severity and SMD diagnosis, and 3) the effects of sex and age. Data were collected through a digital survey (n=1820) and included both high school students (n=924) and university students (n=896). Six different motives were assessed, and SMD was measured in relation to both Heavy Involvement and Negative Consequences of social media use. The results showed that the most common social media use motives were Entertainment, Social Maintenance, and Information & Skills. However, it was the three least common motives -Social Compensation, Self-status, and Escape -that were most strongly associated with SMD symptom severity and SMD diagnosis. These three motives explained as much as 42% of the variance in negative consequences of social media use. Only a few small effects of sex or age were found. In sum, some social media use motives are much more strongly associated with SMD than others are. This could indicate that prevention and intervention programs should target these motives specifically, rather than focusing on social media use in general.